Wephouria Fest 2026 di Tanah Grogot sebagai Bisnis Bazaar-Cultural Event - Ibnu Khayath Farisanu; Wahyudi Wahyudi; Syifi Fauziah; Dedy Darmawan; Indri Farradina; Rusmiati Rusmiati (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2026)
The paradigm shift in higher education requires universities to act as nodes for regional economic growth through experiential learning models. This community service (PkM) program aims to reconstruct a youth cultural event into an institutionally designed bazaar-cultural event to accelerate the capacity of student startup entrepreneurs. The program was integrated into the Wephouria Fest 2026 at STIE Widya Praja Tanah Grogot, Paser Regency, involving alliance consisting of academic institutions, student bodies, alumni, and cross-sector corporate sponsors. The method applied combined community education, interactive mentoring, and institutional space policy facilitation through three phases: situation analysis, clinical on-site mentoring, and mixed-methods outcome evaluation. The results indicated that the program successfully transformed the campus courtyard into a functional "living laboratory" and inclusive trading circuit. Academic intervention effectively reduced students' financial anxiety and significantly improved their financial literacy, with 88% of student entrepreneurs successfully generating simple profit-loss financial statements and managing cash flows under crowded event risks. Furthermore, the festival generated a substantial local economic multiplier effect through direct transactions at student stalls. This program proves that community-based event management can be utilized as a legitimate experiential learning instrument to foster independent young entrepreneurs in rural regions